Integrasi Nilai Moderasi Beragama Dalam Program OSIS untuk Meningkatkan Toleransi antar Siswa di SMA Negeri 1 Parungpanjang - Nasution, Hasiolan; Nisaul Mufidah (STAI Asy-Syukriyyah, 2025)
This research aims to explore the integration of religious moderation in the student council work program to increase tolerance between students at SMA Negeri 1 Parungpanjang. Religious moderation is a strategic approach to building social harmony in the context of a diverse society. This study uses a qualitative method, collecting data through interviews and observations. The study results show that the student council work program that integrates the value of religious moderation is effective in strengthening tolerance attitudes between students. This program has succeeded in creating a positive interaction space between students with different religious, cultural, and ethnic backgrounds. The role of the student council coach is very significant in supporting the implementation of the program. They not only provide direction but also provide an example of practicing religious moderation. This helps students understand the importance of the values of togetherness and mutual respect. Challenges in the implementation of this program include the lack of participation of students who have not fully benefited from the value of religious moderation. This shows that there is a need for innovation in the design of activities to be more inclusive and attractive for all students. The value of religious moderation taught through the student council program not only has an impact on the interaction between students in the school environment but is a long-term contribution to the formation of students' character as inclusive and tolerant individuals.